2014
DOI: 10.1007/s11864-013-0269-x
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Use of Complementary and Alternative Medicine Approaches in Gynecologic Cancers

Abstract: Gynecologic cancer patients frequently desire alternative and/or complementary interventions or medicines to aid in relief of both cancer-related and treatment-related side effects. Furthermore, women also seek treatment to aid in superior outcomes and cure rates. Unfortunately, evidence suggests that the use of complementary and/or alternative medicine (CAM) is underreported or not discussed with physicians providing cancer care. In gynecologic cancer literature, there is a lack of scientific evidence either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Despite advances in diagnosis and treatment, gynecological cancers are still one of the most commonly diagnosed cancers and leading causes of cancer-related death among women worldwide. It has been suggested that traditional medicines, as therapeutic supplements or substitutes for conventional medications, have been frequently used by women with gynecological malignancies in order to improve treatment outcomes and reduce side effects, 22 even if the safety and efficacy of these experience-based medicines are not always evidence based. 23 , 24 Because traditional herbal formulae always contain numerous chemical ingredients with diverse pharmacological activities, the pharmaceutical studies on traditional medicines based on conventional “one drug, one target” concept are extremely resource intensive, time-consuming, and therefore, inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in diagnosis and treatment, gynecological cancers are still one of the most commonly diagnosed cancers and leading causes of cancer-related death among women worldwide. It has been suggested that traditional medicines, as therapeutic supplements or substitutes for conventional medications, have been frequently used by women with gynecological malignancies in order to improve treatment outcomes and reduce side effects, 22 even if the safety and efficacy of these experience-based medicines are not always evidence based. 23 , 24 Because traditional herbal formulae always contain numerous chemical ingredients with diverse pharmacological activities, the pharmaceutical studies on traditional medicines based on conventional “one drug, one target” concept are extremely resource intensive, time-consuming, and therefore, inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…CAM therapies and practices represent a significant and growing aspect of oncology care ( Chase et al, 2014 ). Our study suggests that CAM use in gynecologic oncology patients may be lower than previously suspected and that there is some association between demographic factors and attitudes and beliefs regarding CAM.…”
Section: Discussionmentioning
confidence: 99%
“…Mistletoe extract seems to contain oncologically relevant active substances that exert anticancer effects and appear to prolong overall survival and markedly increase QOL, without the recurrence of cancer or ascites. [7,11] Various clinical studies including matched-pair studies, placebo-controlled and even randomized studies suggests that cancer patients treated with the mistletoe extract had a increased survival rate. [1215]…”
Section: Discussionmentioning
confidence: 99%